MODERN DIRECTIONS OF TEACHING - Eshkoraev Esan; Giyosjon Abdurakhmonov (PEDAGOGS, 2024)
Abstract: – This article is devoted to the introduction of modern directions in the field of language teaching, which fundamentally changes traditional pedagogical approaches. With the development of technology and globalization, the need for more efficient and effective methods of language teaching is increasing. This shift in focus has led to the emergence of innovative strategies and techniques that address the diverse needs and learning styles of students. The introduction of modern trends in language teaching is aimed at improving the overall process of language acquisition, including such elements as communicative language teaching, task-based learning and technology integration. These approaches provide a more immersive and interactive learning environment, emphasizing real-world language use and practical communication skills. By embracing these contemporary trends, educators can better equip students with the linguistic tools and cultural competencies needed to thrive in today's interconnected world.